Total Phenolic Content and Antioxidant Activity of Mung bean Seed Cultivars from Optimized Extraction Treatment - Eriyanto Yusnawan; Sutrisno Sutrisno; Afandi Kristiono (Balai Penelitian Tanaman Aneka Kacang dan Umbi, 2019)
Secondary metabolites are produced by plants both during normal growth and under biotic and abiotic stresses. Apart from genetic and environmental factors, the secondary metabolite contents are also influenced by analytical methods. The aims of this study were to obtain suitable solvents and extraction treatments which produced high total flavonoid and phenolic contents as well as antioxidant activity in shiny and dull green mung beans. An extraction of 0.5 g sample with grade 80 mesh in 70% acetone was selected to estimate the contents of total flavonoids and phenolics. A treatment of shaking the sample in 70% acetone (1:10 w/v) for 2 h and followed by 18 h of maceration with twice extractions showed the highest amounts of flavonoid as well as phenolic contents. Total flavonoid and phenolic contents of 14 mung bean cultivars ranged from 1.28 to 2.35 mg CE/g and 3.74 to 6.58 mg GAE/g, respectively. Antioxidant activity represented by percentage of DPPH inhibition varied from 66.8 to 91.5%. A dull green mung bean cultivar Vima 1 had the highest total flavonoid and phenolic contents (2.35 mg CE/g and 6.58 mg GAE/g). Antioxidant activity of Vima 1 cultivar (91.5%) was not different from those of Perkutut (91.5%), Murai (90.1%) and Sriti (88.9%). The small quantity of sample (0.5 g) combined with the simple extraction treatment was effective in quantifying the different contents of total flavonoids and phenolics in mung bean seeds.